PEMANFAATAN MIKROORGANISME PENGHASIL KOLAGEN SEBAGAI PENGGANTI KOLAGEN BABI DALAM SKIN CARE HALAL - Mayuri, Nindya Sekar; Dianah, Pepin Nur; Asifadilah, Ayu (Politeknik META Industri Cikarang, 2024)
Collagen is a protein material that has tensile strength and a fiber-shaped structure, and is found in many higher vertebrates with an amount of around 25-30% of the protein that makes up the body. Currently, collagen is widely used as a basic ingredient in beauty products. The collagen that is most widely marketed generally comes from the skin and bone tissue of cows or pigs, the safety and halal of which need to receive more attention, so an alternative source of collagen that is safe and halal is needed to replace pork collagen. One alternative that can be used is to use collagen-producing microorganisms. This research uses library research (Library Research) with documentation methods to analyze library results. The results of the analysis show that the bacteria Streptococcus pyrogenes is a potential bacteria that can be used to replace pork collagen. Recombinant technology by manipulating the hCol gene as human collagen and bCol as recombinant bacterial collagen Scl2. This manipulation can optimize molecular and biological properties. Apart from that, to increase the stability of the S.pyrogenes Scl2 bacterial collagen, the insertion of hydroxyproline was carried out by combining direct co-translation of modified amino acids using the codon for proline in inserting the gene construction. This GMO (Genetically Modified Organism) product is certainly halal because it does not use ingredients containing pork.